Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

Solve 3x2 18x 15 = 0 by completing the square. a. 3(x 3)2 = 6; x = −3 square root 2, x = −3 − square root 2 b. 3(x 9)2 = 12; x = −11, x = −7 c. 3(x 3)2 = 12; x = −5, x = −1 d. 3(x 9)2 = 228; x = −9 square root 76, x = −9 − square root 76

Donald Ward

in Mathematics

follow
followin
1 answer
5 views

1 answer


Samantha Barber on January 4, 2019

3(x^2 + 6x + 5) = 03(x^2 + 6x + 9 + 5 - 9) = 03(x + 3)^2 + 3(-4) = 03(x + 3)^2 - 12 = 03(x + 3)^2 = 12(x + 3)^2 = 4x + 3 = sqrt(4)x = -3 + or - 2x = -3 + 2 -3 or - 2x = -1 or -5the correct answer option is option c.


Add you answer